2021
DOI: 10.1186/s42649-021-00055-w
|View full text |Cite
|
Sign up to set email alerts
|

Fractal dimension analysis as an easy computational approach to improve breast cancer histopathological diagnosis

Abstract: Histopathology is a well-established standard diagnosis employed for the majority of malignancies, including breast cancer. Nevertheless, despite training and standardization, it is considered operator-dependent and errors are still a concern. Fractal dimension analysis is a computational image processing technique that allows assessing the degree of complexity in patterns. We aimed here at providing a robust and easily attainable method for introducing computer-assisted techniques to histopathology laboratori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Their investigation revealed that fractal dimension-based features extracted from stained WSI demonstrated remarkable capabilities in distinguishing breast carcinomas from normal tissue and benign breast alterations. These findings underscore the significance of fractal dimension analysis as a powerful tool in advancing our understanding and diagnostic capabilities in histopathological studies [75] .…”
Section: Discussionmentioning
confidence: 72%
“…Their investigation revealed that fractal dimension-based features extracted from stained WSI demonstrated remarkable capabilities in distinguishing breast carcinomas from normal tissue and benign breast alterations. These findings underscore the significance of fractal dimension analysis as a powerful tool in advancing our understanding and diagnostic capabilities in histopathological studies [75] .…”
Section: Discussionmentioning
confidence: 72%
“…These findings underscore the significance of fractal dimension analysis as a powerful tool in advancing our understanding and diagnostic capabilities in histopathological studies. 64…”
Section: Discussionmentioning
confidence: 99%
“…These findings underscore the significance of fractal dimension analysis as a powerful tool in advancing our understanding and diagnostic capabilities in histopathological studies. 64 It is important to note that the histopathological analysis of breast cancer that we used as test case of our Digital Pathology approach can be critical due to its intrinsic complexity. Indeed, cell density and morphology alone cannot be sufficient for the differential diagnosis between a malignant and a benign lesion, as special cases such as florid adenosis or sclerosing adenosis could create outputs that may be associated with false-positive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Fractal analysis is already used to study cancer [ 15 , 16 ], and it can lead to the improvement of the diagnostic validity of both cyto-histopathological and medical imaging findings [ 17 ]. For instance, fractal analysis has been used to elucidate various types of tumors: colorectal cancer (CRC) [ 18 ]; rectal cancer [ 19 ]; and breast cancer [ 20 , 21 , 22 ], to name a few. The fractal or Hausdorff dimension (FD) [ 23 ] is the index that has been used the most in cancer analysis.…”
Section: Introductionmentioning
confidence: 99%